2013
DOI: 10.1021/ac401599t
|View full text |Cite
|
Sign up to set email alerts
|

Displacement-type Quartz Crystal Microbalance Immunosensing Platform for Ultrasensitive Monitoring of Small Molecular Toxins

Abstract: A novel displacement-type quartz crystal microbalance (QCM) immunosensing strategy, based on glucose and its analogue dextran for concanavalin A (ConA) binding sites, was designed for ultrasensitive monitoring of small molecular biotoxins (brevetoxin B, PbTx-2, used as a model) with signal amplification on a graphene-functionalized sensing interface. To construct such a QCM immunosensing platform, phenoxy-functionalized dextran (DexP) was initially assembled onto the surface of graphene-coated QCM probe via th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 44 publications
(71 reference statements)
1
41
0
Order By: Relevance
“…It was reported that a graphene functionalized sensing-based biosensor combined with a quartz crystal microbalance immunosensor was used t to detect BTX [82]. A dendrimer decorated with gold nanoparticles was used to fabricate electrochemical immunosensors to detect BTXs [83].…”
Section: The Detection Of Representative Marine Toxins By Aptasensorsmentioning
confidence: 99%
“…It was reported that a graphene functionalized sensing-based biosensor combined with a quartz crystal microbalance immunosensor was used t to detect BTX [82]. A dendrimer decorated with gold nanoparticles was used to fabricate electrochemical immunosensors to detect BTXs [83].…”
Section: The Detection Of Representative Marine Toxins By Aptasensorsmentioning
confidence: 99%
“…Up to date, various methods and strategies based on different signal-transducer principles have been reported and developed for this purpose, e.g. by using surface plasmon resonance, quartz crystal microbalance, electrochemiluminescence, fluorescence (FL), chemiluminescence (CL), electrochemistry and colorimetric method891011121314. Typically, the colorimetric method is the most commonly used method in immunoassays because of several important advantages, e.g.…”
mentioning
confidence: 99%
“…5B). Obviously, the LOD of our strategy was even lower than those of cardiomyocyte-based potential biosensor (1.5 ng mL -1 ) (Wang et al, 2015), enzyme-free electrochemical immunoassay (5 pg mL -1 ) (Lin et al, 2015b), aptamer-based competitive electrochemical biosensor (106 pg mL -1 ) (Eissa et al, 2015), Ag(I)-TMB-based colorimetric immunoassay (0.1 ng kg -1 ) (Lai et al, 2015), hollow gold nanosphere-based immunodipstick (0.1 ng mL -1 ) (Zhang et al, 2014), homogenous electrochemical immunoassay (6 pg mL -1 ) , displacement-type quartz crystal microbalance immunoassay (1.0 pg mL -1 ) (Tang et al, 2013), capillary electrophoresis-based immunoassay (0.1 ng mL -1 ) , glucose meter-based assay (0.1 ng mL -1 ) (Gao et al, 2014b) and commercialized BTB ELISA kit from Abraxis LLC Inc. (50 ng kg -1 ). Due to the legal limit of brevetoxin (≤ 80 μg of toxin per 100 g of shellfish tissue) (Hunt et al, 1979;Trainer et al, 1991), the Fenton reaction-based colorimetric immunoassay could completely meet the need of BTB monitoring in seafood.…”
Section: Analytical Performance Of Fenton Reaction-based Colorimetricmentioning
confidence: 99%